Konstruksi berpikir Hakim dalam Menerapkan Asas Lex Specialis Systematisch Terhadap Penegakan Hukum Tindak Pidana Korupsi - Dara Yanita Haq (JOURNAL EQUITABLE, 2020)
Establishment of special laws that are outside the sectoral specific Criminal Code. Each rules according to the sector. This condition has the potential of one another. To determine which Special Law is applied, then the principle of lex specialis systematisch or systematic specificity applies. in the decision of the issued verdict, the decision of the decision that did not include the principle of lex specialis systematisch was not included. Where the principle of lex specialis systematisch must be applied to the verdict. How to determine the difference in assessment in applying the principle of lex specialis systematisch is because of a different understanding of State Financial Losses by law enforcers relating to their attitudes and judgments.